Análise da prevalência de sífilis gestacional no Nordeste do Brasil: uma abordagem multifatorial - Cavalcante, Jéssica Beatriz Pachêco (2025)
Syphilis is a chronic and systemic bacterial infection caused by Treponema pallidum, primarily transmitted through sexual contact. The disease can also be vertically transmitted from mother to fetus during pregnancy, potentially causing severe health consequences for the baby, including miscarriage, stillbirth, congenital deformities, and neurological impairments. Given the severity of these complications, epidemiological surveillance of syphilis in pregnant women is essential to prevent and control the spread of the disease, protecting the health of both mothers and their babies. Therefore, this study aimed to analyze the estimated prevalence of syphilis in pregnant women in Northeast Brazil from 2017 to 2022 using a geospatial approach. This study is characterized as ecological, adopting a quantitative, descriptive, and explanatory approach. The adopted method involved the application of statistical models to estimate the disease prevalence in each state of the Northeast and the generation of choropleth maps to visualize the geographic distribution of cases over time. Data from 1,794 municipalities in the region Northeast were analyzed, and the results revealed a complex dynamic in the spread of syphilis, with variations in case distribution over the years, without a specific location showing consistently higher prevalence. The spatial analysis of the data allowed the identification of areas with higher prevalence rates in different periods, highlighting the importance of an adaptive approach to disease control. The generated choropleth maps provided a valuable tool for health managers, enabling a clear and accessible visualization of syphilis distribution and assisting in strategic decision-making and efficient resource allocation. Additionally, the results contributed to a deeper understanding of the epidemiology of syphilis in Northeast Brazil, providing insights for the development of more effective and targeted health policies and programs. In conclusion, this study demonstrated that syphilis in pregnant women remains a significant public health challenge in Northeast Brazil, with complex spatial and temporal distribution patterns. Data analysis highlighted the need for flexible and adaptive strategies in disease control, as well as the importance of choropleth maps in visualizing and interpreting prevalence patterns. These findings provide crucial support for the formulation of health policies and actions aimed at preventing and controlling syphilis, protecting the health of pregnant women and their babies, and Northeast Brazil.